Bipedicled Flap for the Reconstruction of Soft Tissue Defects of the Achilles Tendon. Issue 4 (April 2015) - Lin, Chin-Ta; Chen, Shyi-Gen; Chen, Tim-Mo; Dai, Niann-Tzyy; Chang, Shun-Cheng
Abstract : Abstract: Soft tissue defects exposing the Achilles tendon are common in patients who have undergone trauma or in those with pressure ulcers associated with vascular diseases. The purpose of this article was to present our experience of 11 patients who underwent reconstruction of soft tissue defects of the Achilles tendon using bipedicled fasciocutaneous flaps. Between August 2008 and August 2012, 11 patients were admitted to our hospital, presenting with soft tissue defects overlying the Achilles tendon. After adequate debridement, the 11 patients underwent bipedicled fasciocutaneous flap placement to resurface the complex soft tissue defects and provide a gliding surface for the exposed Achilles tendon. The patients' age, comorbidity, etiology, defect size and location, wound culture, skin graft size, complications, surgery duration, and follow-up period were reviewed. The 11 fasciocutaneous bipedicled flaps survived completely, and the wounds healed satisfactorily at a mean follow-up period of 20.9 months (range, 6-48 months). Only 1 flap was complicated with wound dehiscence and superficial necrosis of its lateral edge, which healed conservatively. The donor sites were covered with split-thickness skin grafts and healed well without complications. The bipedicled fasciocutaneous flap is a reliable flap for coverage of defects overlying the Achilles tendon, especially in patients with vascular problems and/or elderly patients. The ease of handling, short operative time, and early recovery of mobilization function are of great benefit to patients. Thus, the bipedicled fasciocutaneous flap can be a valuable alternative for defect reconstructions overlying the Achilles tendon, with satisfactory results both functionally and cosmetically.